Hak Nafkah Isteri (Perspektif Hadis dan Kompilasi Hukum Islam) - Hudaya, Hairul (Jurnal Muadalah, 2013)
Hadith, as a second source of Islamic laws after the Qurâan, contains various provisions of the laws, including the rights of wifes livelihood. Meanwhile, in the context of law in Indonesia, Compilation of Islamic Laws is used as the legal basis in settling lawsuits in Religious Courts. The Compilation of Islamic Laws is compiled with considering the moeslem scholars thought especially they who adhere to al-Syafiâi notion. The theologians themselves are oriented to the Qurâan and Hadith in defining laws. Then, are there any differences between the laws products in the Compilation of Islamic Laws and the source of Islamic laws especially hadith concerning livelihood issues? It is found that the difference is when the wifes commit nusyuz, their reights will be eliminated. The notion is more likely based on the scholars judgement and it is not clearly elaborated in the Hadith.Keywords: livelihood, Compilation of Islamic Laws, nusyuzHadis, sebagai sumber hukum Islam kedua setelah Alquran, memuat berbagai ketentuan hukum termasuk dalam masalah hak nafkah isteri. Sementara itu, dalam konteks hukum di Indonesia, KHI menjadi dasar hukum dalam menyelesaikan perkara di lingkungan Peradilan Agama. KHI disusun dengan mempertimbangkan pemikiran para ulama terutama bermazhab al-Sya>fiâi>. Sedang ulama mazhab sendiri dalam menetapkan hukum tidak terlepas dari Alquran dan hadis. Lantas, adakah perbedaan antara produk hukum dalam KHI dengan sumber hukum Islam terutama hadis dalam masalah nafkah? Sejauh ini, perbedaan tersebut terletak pada gugurnya hak nafkah isteri apabila ia berlaku nusyuz. Pandangan tersebut lebih didasarkan pada pendapat ulama mazhab karena tidak ditemukan dasarnya secara tegas dan jelas dalam sejumlah kitab hadis.Kata Kunci: nafkah, Kompilasi Hukum Islam, nusyuz.